Derrida's Politics of Friendship Amity and Enmity. - Collison, Luke (Edinburgh University Press, 2022)
25 years after the publication of Derrida's Politics of Friendship (Politiques de l'amitié, 1994), this edited collection gathers 23 critical chapters that revisit this underappreciated text. Engaging closely with Derrida's text, the contributors analyse, extend and critique the work.